Utilizing Shear Factor Model and Adding Viscosity Term in Improving a Two-Dimensional Model of Fluid Flow in Non Uniform Porous Media - Bindar, Yazid; Makertihartha, IGBN; Supardan, M. Dani; Buchori, Luqman (ITB Journal Publisher, LPPM ITB, 2007)
In a packed bed catalytic reactor, the fluid flow phenomena are very complicated because the fluid and solid particle interactions dissipate the energy. The governing equations were developed in the forms of specific models. The shear factor model was introduced in the momentum equation for covering the effect of flow and solid interactions in porous media. A two dimensional numerical solution for this kind of flow has been constructed using the finite volume method. The porous media porosity was treated as non-uniform distribution in the radial direction. Experimentally, the axial velocity profiles produce the trend of having global maximum and minimum peaks at distance very close to the wall. This trend is also accurately picked up by the numerical result. A more comprehensive shear factor formulation results a better velocity prediction than other correlations do. Our derivation on the presence of porous media leads to an additional viscosity term. The effect of this additional viscosity term was investigated numerically. It is found that the additional viscosity term improves the velocity prediction for the case of higher ratio between tube and particle diameters